Ketekunan Dalam Iman : Eksplorasi Teologis Pengharapan Kristen Ditengah Ujian Berdasarkan Yakobus 1:2-3 - Yurniwati Waruwu; Malik Bambangan (Jurnal Silih Asuh : Teologi dan Misi, 2025)
important. Based on James 1:2-3, this paper explores Christian expectations and the role of perseverance in shaping spiritual character. The background of this study arises from the importance of understanding perseverance as a response to trials faced by individuals of faith. The purpose of this study is to investigate how perseverance in faith is formed and developed through challenges, as well as its impact on Christian hope. This research used a qualitative method with a literature study approach. Data was collected from library sources, including books of biblical interpretation and relevant theological articles. The results showed that perseverance is not just a passive attitude but an active process that deepens faith and hope. The discussion focused on the role of trials as a tool used by God to strengthen the faith of believers, as described in James 1:2-3. Trials are seen as a way to sharpen perseverance, which then leads to spiritual maturity and strong hope. This study affirms the importance of seeing trials as an essential part of the Christian faith journey that ends in eternal hope.